2005
DOI: 10.1093/humrep/deh898
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subfertility cause, smoking and body weight on the success rate of IVF

Abstract: Both smoking and overweight unfavourably affect the live birth rate after IVF. The devastating impact of smoking on the live birth rate in IVF treatment is comparable with an increase in female age of >10 years from age 20 to 30 years. Subfertile couples may improve the outcome of IVF treatment by lifestyle changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
6
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(130 citation statements)
references
References 25 publications
(30 reference statements)
6
112
6
4
Order By: Relevance
“…All the subjects had to fulfil the following inclusion criteria: (1) regular menstrual cycles (28-35 days), (2) first ovarian stimulation treatment, (3) both ovaries visualised on transvaginal ultrasound, (4) no use of hormone therapy in the 6 months before entering the study, (5) no history of premature ovarian failure and/or autoimmune diseases, (6) no previous ovarian surgery, (7) no exposure to cytotoxic drugs or pelvic radiation therapy, and (8) BMI>19< 30 kg/m 2 . Written informed consent was obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the subjects had to fulfil the following inclusion criteria: (1) regular menstrual cycles (28-35 days), (2) first ovarian stimulation treatment, (3) both ovaries visualised on transvaginal ultrasound, (4) no use of hormone therapy in the 6 months before entering the study, (5) no history of premature ovarian failure and/or autoimmune diseases, (6) no previous ovarian surgery, (7) no exposure to cytotoxic drugs or pelvic radiation therapy, and (8) BMI>19< 30 kg/m 2 . Written informed consent was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…There is also evidence that smoking negatively impacts on all areas of fertility from follicle development to fertilization and embryo cleavage. When in vitro fertilization (IVF) is used, fewer follicles are stimulated, fewer oocytes are retrieved, implantation rates are lower, more cycles are cancelled and live birth rates are significantly lower in smokers when compared to non-smokers [5][6][7][8]. Interestingly, passive smoking is found to be just as detrimental to fertility as active smoking, halving the pregnancy rate [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence is conflicting regarding the effect that obesity has on live birth rates in assisted reproductive outcomes. Studies have shown lower clinical pregnancy rates, higher miscarriage rates, and decreased live birth rates in women with an elevated body mass index [9,[12][13][14]. Other studies, however, have shown no difference in live birth rates when comparing IVF outcomes between normal-weight and obese patients [7,8,15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a number of reports have highlighted the influence of ethnicity on outcome of IVF treatment, [15][16][17][18][19] ), although the direction of its impact (positive or negative) is unclear, mainly due to the small number of patients from [20][21][22][23] Likewise, the presence of uterine fibroids has been shown to reduce the implantation and pregnancy potential after IVF 24,25 and is more common in certain racial groups. The primary cause of infertility, a factor reported to have an impact on IVF outcome 11,26,27 was also different in the two studied groups.…”
Section: Discussionmentioning
confidence: 99%